Towards Understanding Islam - Maudoodi, Syed Abul ʻAla, 1903-1979; Translated and Edited by Khurshid Ahmad (Lahore Islamic Publications Limited, 1973)
A simple, comprehensive introduction to Islam by a noted Muslim of the 20th Century, Sayyid Abul A'la Mawdudi
Include Index
Keywords: Islam